Effect of Gas Phase Heat Sink on Suppression of Opposed Flow Flame Spread over Thin Solid Fuels in Microgravity Environment. (14th November 2012) - Malhotra, Vinayak; Kumar, Chenthil; Kumar, Amit
Abstract : A two-dimensional numerical model of opposed flow flame spread over thin solid fuel is formulated and modeled to study the effect of gas phase heat sink (a wire mesh placed parallel to the fuel surface) on the flame-spread rate and flame extinction. The work focuses on the performance of the wire mesh in microgravity environment at an oxygen concentration 21%. The simulations were carried out for various mesh parameters (wire diameter, "d ¯ w r " and number of wires per unit length, "N ") and mesh distance perpendicular to fuel surface "Y m e s h ". Simulations show that wire mesh is effective in reducing flame-spread rate when placed at distance less than flame width (which is about 1 cm). Mesh wire diameter is determined not to have major influence on heat transfer. However, smaller wire diameter is preferred for better aerodynamics and for increasing heat transfer surface area (here prescribed by parameter "N "). Flame suppression exhibits stronger dependence on number of wires per unit length; however, it is relatively insensitive to number of wires per unit length beyond certain value (here 20 cm −1 ).